QARAQALPAQSTANNÍŃ SOCIAL-EKONOMIKALÍQ HÁM EKOLOGIYALÍQ RAWAJLANÍW TARIYXÍNDAǴÍ AYÍRÍM BAǴDARLARÍ - Djumageldiev, N.R. (SCIENCE and SOCIETY, 2025)
The article presents the results of an analysis of the processes of socio-economic and ecologic development of Karakalpakstan and a historical analysis of changes in social life. The basis of the economy of Karakalpakstan, aimed at the development of market relations, is the property in various forms, taking into account the priority of consumer rights, the state guarantees freedom of economic activity, entrepreneurship and labor, equal rights and equal legal protection of all forms of ownership.